The effect of willow diversity on insect herbivory and predation. (12th August 2021) - Kollberg, Ida; Weih, Martin; Glynn, Carolyn
Abstract: The relationship between plant diversity and ecosystems functions such as regulation of insect herbivory is complex and context‐dependent. The empirical data necessary to account for these interactions are scarce. Our objective is to test the top‐down effects of predation and bottom‐up effects of plant traits to understand what drives patterns of herbivory in managed systems. We established single‐ and multiple‐variety willow field plots with up to four varieties, to study herbivory and predation, and greenhouse experiments to investigate the effects on insect preference and performance. Herbivore damage in the field was higher in single‐ as opposed to multiple‐variety plots for the two most prevalent insect types in one of the 3 years. Predation was higher in multiple‐variety plots than in pure plots during 2016 but the opposite occurred in 2018. Predation on leaf beetle eggs was higher in multiple‐variety plots, but the result was related to specific variety mixtures rather than increased numbers of varieties. Leaf beetle feeding choice and egg‐laying were influenced to some extent by plant diversity. Our results give insights into the links between plant diversity, composition and levels of herbivore damage. They also spark questions about how temporal aspects influence these links.